2001
DOI: 10.1007/pl00002417
|View full text |Cite
|
Sign up to set email alerts
|

3 Jahre Erfahrung mit der niedrig dosierten fraktionierten perkutanen Teletherapie bei subfoveolären Neovaskularisationen Klinische Ergebnisse

Abstract: There is an influence of low dose fractionated percutaneous teletherapy on visual acuity, subfoveal neovascular membranes and metamorphopsia. IVA and duration of anamnesis play an important role. There seems to be no persistent effect; possibly increased dosage will bring a benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2002
2002
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…Die Strahlentherapie gutartiger Erkrankungen wird seit Jahrzehnten durchgeführt. Die erforderlichen Strahlendosen, Fraktionierungen und Therapieergebnisse, aber auch Nebenwirkungen müssen bekannt sein, um eine richtige Behandlungsindikation stellen zu kön- nen [2,8,15,16,18,19]. Die Ergebnisse der Patterns of Care Study bei Keloidtherapie dienen damit auch einer eigenen Qualitätskontrolle.…”
Section: Diskussionunclassified
“…Die Strahlentherapie gutartiger Erkrankungen wird seit Jahrzehnten durchgeführt. Die erforderlichen Strahlendosen, Fraktionierungen und Therapieergebnisse, aber auch Nebenwirkungen müssen bekannt sein, um eine richtige Behandlungsindikation stellen zu kön- nen [2,8,15,16,18,19]. Die Ergebnisse der Patterns of Care Study bei Keloidtherapie dienen damit auch einer eigenen Qualitätskontrolle.…”
Section: Diskussionunclassified
“…This is comparable to the expected natural course. 10 There was a clear drop of VA 12-18 months after radiotherapy as has been shown by Schittkowski et al 34 Considering a possible dose relationship, 5,21,25,35 in this institution, the dose was raised to 20 Gy in 10 fractions in 1998. Only mild acute radiation effects (transient tearing) were observed.…”
mentioning
confidence: 55%
“…Another German study of 27 patients concluded that RT with a total dose of 20 Gy failed to control growth in membrane size both in classic and occult CNV [5]. After irradiation of 118 patients with 20 Gy, Schittkowski et al did not find a persistent effect on vision [21]. Thölen et al treated 53 patients with 10 and 36 Gy in five and 18 fractions, respectively [26].…”
Section: Discussionmentioning
confidence: 99%